Deus está de volta! a influência pública das religiões e o caminho proposto pela BNCC à cultura de paz a partir do ensino religioso - Santos, Tiago Fermino dos (2022)
This dissertation consists of an effort to explain as religions as a significant factor in the human constitution, the ways in which they influence cultural assumptions and how their multiple manifestations contributed to promote peace and also to prevent it from happening at different moments in history, even in Secular States. Religion is presented as a field in permanent dispute by different ideological actors, conflicts that go beyond the private spaces of temples to be equally fought in the public spaces of society, in some cases converting into authoritarian outbursts or armed movements. In this way, religious illiteracy is problematized as an aegis of this sectarianism and literacy is proposed through non-denominational Religious Literacy, according to the parameters of the BNCC, as a response to fundamentalism and as a possible way to educate for a culture of peace. To achieve the objectives, the method of analysis of conjuncture and peace studies was used, in order to understand how the process of construction of the curriculum of Religious Education in Brazil took place and to analyze different expressions of conflicts crossed by religious issues, drawing parallels between religious illiteracy, the escalation of violence in Brazil and in the world, and religious literacy as an essential instrument in the process of building a culture of peace.